Study the effect of gamma radiation on the some properties of glass and glass-ceramic immobilize nuclear waste - Al-Mashhadani, Asia H. (Iraqi Journal of Physics, 2019)
Vitrifications process one of the important methods to immobilize nuclear waste. In this research nuclear waste (Strontium Oxides) with molecular weight (5%) was immobilized by vitrification methods in two types of borosilicate glass (c-type) which are glass and glass-ceramics. To investigate the physical, chemical and mechanical properties of glass and glass-ceramic after immobilize nuclear waste these samples irradiated by gamma ray radiation. Co-60 was used as gamma a irradiation with dose rate 0.38 kGy/hr for different period of time. It’s found that gamma radiation affected the glass and glass-ceramic properties. From phase analysis by the x-ray diffraction for glass-ceramic samples proved that at doses 343kGy change the crystalline glass to amorphous glass. A conclusion from these ionization studies is that the limited magnitude of Strontium ion leaching associated with ionization damage does not appear to pose any direct problems for the safe storage of nuclear waste glass.